Connected Worlds - Kühnhardt, Ludger. author. aut Link
XXXVI, 554 p. 51 illus., 2 illus. in color.
Keywords: The diary notes that Ludger Kühnhardt took while visiting or staying in 235 countries and territories around the world create a fascinating panorama, reflected in the personal impressions, encounters and experiences of a political scientist and journalist working all over the world. The book reconstructs the connections between Europe's transformations and the emerging global era over six decades from 1960 to the threshold of the post-Corona world of 2020. The author Dr. Ludger Kühnhardt is director at the Center for European Integration Studies (ZEI) and professor of political science at Bonn University, Germany. The translation was done with the help of artificial intelligence. A subsequent human revision was done primarily in terms of content. .